USING BOOKS IN ADDRESSING THE SOCIO-EMOTIONAL PROBLEMS OF CHILDREN WITH HEARING IMPAIRMENT (Proceedings of the International Conference on Education, 2019)
The lack of communication skills in children with hearing impairment poses difficulties in the detection and management of their socio-emotional issues. Unaddressed, these could negatively impact school performance. In search for possible interventions, an exploratory research used mixed methods to look into the use of books and read aloud activities using sign language. It sought to establish: 1. How the teachers select books for relevance, conduct the reading sessions, elicit responses from the hearing impaired children and process their issues; and 2. How the children with hearing impairment benefit from such activity. Of thirty (30) teachers surveyed, six (6) had previous training in therapeutic interventions and were using book therapy at the time of the study. Critical purposive sampling, the teachers were selected as respondents in case studies, along with six (6) hearing impaired children who were experiencing communication, anxiety and self-concept issues. The study employed a triangulation of the following methods: in-depth interviews and non-participant class observation of read aloud activities. Findings suggests that: 1. Reading material selection takes into consideration hearing impairment and the presenting socio-emotional issues of the students; 2. Books are low cost effective therapy tool, but locally produced ones depicting Filipino characters are hard to come by; 3. Read aloud activities are enhanced by the use of art activity and role playing, allowing the students to express themselves in variety of ways; and 4. Discussion allows the students to express how they relate with the characters, understand their issues better and works towards problem solving. The writing of books depicting Filipino characters and the conduct of more researches on the topic are recommended.
Keywords: Socio-Emotional Problems; Read Aloud; Children with Hearing Impairment